PERAN LITERASI BUDAYA DALAM SASTRA LISAN - Siti Masitoh (Jurusan Sastra Indonesia, Fakultas Sastra, Universitas Negeri Malang (UM), 2017)
Texts cannot be separated from its context in order to reach the deeper understanding of the text’s significances. The same is thrue with the text of Murwakala . The readers will be able to get better understanding of Murwakala’s significances when the readers have got sufficient knowledge of wayang (shadow theater) and ruwatan. It happens because the Javanese have certain way how to have a look wayang. This article is aimed at presenting the importance of having cultural literacy in understanding the significance of the oral tradition.